Regional tourism competitiveness using the PROMETHEE approach. - Lopes, Ana Paula; Muñoz-Martos, María del Mar; Alarcón-Urbistondo, María del Pilar (Elsevier, 2018)
The competitiveness of tourism destinations is a key issue because it enables destinations to know their position with regard to their competitors. The aim of this paper is threefold: (1) to address the measurement of the competitiveness of tourism destinations at the regional level, (2) to show the suitability of using multi-criteria techniques to measure competitiveness, and (3) to apply the PROMETHEE and GAIA methods within a competitiveness study of eight tourist destinations located in the Northern Region of Portugal. The Metropolitan Area of Porto is the first in the ranking, followed by Cávado and Douro. The results of such an analysis show the comparative strengths and weaknesses of destinations, and allow them to identify their true competitors as well as those other destinations that are most similar to them
Política de acceso abierto tomada de: https://openpolicyfinder.jisc.ac.uk/id/publication/10583
Keywords: Competencia económica; Turismo - Modelos econométricos; Destination competitiveness; Competitiveness Index; PROMETHEE-GAIA; Multi-criteria decision making